Analysis of the aerodynamics by experimental testing of an elite wheelchair sprinter - Barbosa, Tiago M. (2016)
One concern for wheelchair sprinters is the head’s alignment racing. This misalignment may increase significantly the resistance acting upon the athlete albeit, evidence on this is scarce in wheelchair racing. A feasible way to gather insight on the effects of misalignments in the aerodynamics is the cost-down technique.